A comparison between mometasone furoate nasal spray and intranasal glycyrrhetic acid in patients with allergic rhinitis: a preliminary study in clinical practice - Gariuc, Lucia; Sandul, Alexandru; Rusu, Daniela; Passali, Desiderio; Bellussi, Luisa Maria; Damiani, Valerio; Ciprandi, Giorgio (Acta Biomedica Atenei Parmensis, 2020)
Allergic rhinitis (AR) is caused by an IgE-mediated inflammatory reaction consequent to the exposure to the causal allergen. Glycyrrhetic acid (GlyAc) is a natural compound extracted from the liquorice that exerts anti-inflammatory activity. This real-life study compared intranasal GlyAc, present in a medical device containing also glycerol and mannitol, with mometasone furoate nasal spray (MFNS) in 50 adult outpatients with AR. Both treatments lasted 2 months. Endoscopic signs, perception of symptom severity, assessed by VAS, and nasal function measured by rhinomanometry were evaluated at baseline (T0), after one (T1) and two (T2) months. The intergroup analysis showed that at T1 there was no significant difference between groups about the use of decongestants and antihistamines, turbinate hypertrophy and pale mucosa, perception of olfaction and snoring. At T2 there was no significant difference between groups about use of relievers, all endoscopic signs, and perception of nasal discomfort, nasal obstruction, olfaction, and snoring. The intragroup analysis showed that in MFNS group there was a significant change during the entire period of treatment for all parameters except watery rhinorrhea (sign) and ocular discomfort; in GlyAc group there was a significant change during the entire period of treatment for all parameters. In conclusion, this preliminary study, conducted in clinical practice, evidenced that intranasal CysAC plus mannitol was able to significantly improve nasal endoscopic signs, perception of symptoms, and nasal function in patients with AR. Therefore, GlyAc could be a reasonable therapeutic option to control allergic inflammation.